2020
DOI: 10.1038/s41423-020-0372-4
|View full text |Cite
|
Sign up to set email alerts
|

A novel coronavirus (2019-nCoV) causing pneumonia-associated respiratory syndrome

Abstract: By the end of 2019, the World Health Organization (WHO) was informed about an outbreak of pneumonia of unknown etiology in Wuhan, China. Some patients were linked to a seafood market, suggesting animal-to-human transmission, but, soon, human-tohuman transmission was confirmed. The pathogen was promptly identified as a novel coronavirus belonging to lineage B betacoronaviruses that also include severe acute respiratory syndrome coronavirus (SARS-CoV), which caused a pandemic in China in 2002/2003, and bat SARS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
150
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(156 citation statements)
references
References 3 publications
2
150
0
4
Order By: Relevance
“…Until now, six human coronaviruses (HCoVs) have been identified, namely, HCoV-229E, HCoV-HKU1, HCoV-OC43, HCoV-NL63, severe acute respiratory syndrome coronavirus (SARS-CoV), and Middle East respiratory syndrome coronavirus (MERS-CoV) [4]. In particular, SARS-CoV and MERS-CoV once caused pandemic [5].…”
Section: Introductionmentioning
confidence: 99%
“…Until now, six human coronaviruses (HCoVs) have been identified, namely, HCoV-229E, HCoV-HKU1, HCoV-OC43, HCoV-NL63, severe acute respiratory syndrome coronavirus (SARS-CoV), and Middle East respiratory syndrome coronavirus (MERS-CoV) [4]. In particular, SARS-CoV and MERS-CoV once caused pandemic [5].…”
Section: Introductionmentioning
confidence: 99%
“…Corona Virus Disease 2019 (COVID-19) is a recently emerged life-threatening viral pneumonia disease caused by SARS-CoV-2 (named 2019-nCoV before February 11, 2020) (1). COVID-19 is spreading worldwide, and as of February 29, 2020, approximately 80,000 confirmed cases had been identified in the world.…”
Section: Introductionmentioning
confidence: 99%
“…In December 2019, a cluster of patients with pneumonia of unknown etiology was reportedly linked to Huanan Seafood Wholesale Market in Wuhan, Hubei Province, China. [1][2][3][4] Soon after, it was confirmed that this pneumonia was caused by infection of a novel pathogen [5], Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), as recently named by the World Health Organization, and the disease caused by such virus infection, the Corona Virus Disease 2019 (COVID-19) [6]. In January 2020, a widespread outbreak of COVID-19 occurred following the beginning of the largest annual migration in China known as the Spring Festival migration.…”
Section: Main Textmentioning
confidence: 99%
“…The first order functions of time and R0 were obtained with the method of least square. Considering the objective first order function as aT+b=R0, where T was number of time windows from starting one, and a, b are parameters to be fitted, the sum of deviations squared from the given set of data was calculated by (2).…”
Section: Evaluation and Comparison Of Change Of R0mentioning
confidence: 99%